Improving quality of surgical and anaesthesia care in sub-Saharan Africa: a systematic review of hospital-based quality improvement interventions - Justine Davies; Nataliya Brima; Imran O Morhason-Bello; Andy JM Leather; Vandy Charles (BMJ Open)
Objectives To systematically review existing literature on hospital-based quality improvement studies in sub-Saharan Africa that aim to improve surgical and anaesthesia care, capturing clinical, process and implementation outcomes in order to evaluate the impact of the intervention and implementation learning.Design We conducted a systematic literature review and narrative synthesis.Setting Literature on hospital-based quality improvement studies in sub-Saharan Africa reviewed until 31 December 2021.Participants MEDLINE, EMBASE, Global Health, CINAHL, Web of Science databases and grey literature were searched.Intervention We extracted data on intervention characteristics and how the intervention was delivered and evaluated.Primary and secondary outcome measures Importantly, we assessed whether clinical, process and implementation outcomes were collected and separately categorised the outcomes under the Institute of Medicine quality domains. Risk of bias was not assessed.Results Of 1573 articles identified, 49 were included from 17/48 sub-Saharan African countries, 16 of which were low-income or lower middle-income countries. Almost two-thirds of the studies took place in East Africa (31/49, 63.2%). The most common intervention focus was reduction of surgical site infection (12/49, 24.5%) and use of a surgical safety checklist (14/49, 28.6%). Use of implementation and quality improvement science methods were rare. Over half the studies measured clinical outcomes (29/49, 59.2%), with the most commonly reported ones being perioperative mortality (13/29, 44.8%) and surgical site infection rate (14/29, 48.3%). Process and implementation outcomes were reported in over two thirds of the studies (34/49, 69.4% and 35, 71.4%, respectively). The most studied quality domain was safety (44/49, 89.8%), with efficiency (4/49, 8.2%) and equitability (2/49, 4.1%) the least studied domains.Conclusions There are few hospital-based studies that focus on improving the quality of surgical and anaesthesia care in sub-Saharan Africa. Use of implementation and quality improvement methodologies remain low, and some quality domains are neglected.PROSPERO registration number CRD42019125570